Protean supply chains ten dynamics of supply and demand alignment - Cooke, James A. (Hoboken, New Jersey Wiley, 2014)
"This book features ten emergining trends that are shaping supply chain operations worldwide and imapcting the global business landscape. These trends include: the rise of regional theatres of supply; managing global risk through control towers; customer segmentation; realizing real demand; multi-channel challenges; aligning demand swings with production and distribution; serving a customer of one; the sustainability petard; collaboration vs. competition in the new economy; and financial dynamism. In addition, the book features an introduction to the overlooked supply chain factor behind anemic economic growth and an overview of protean supply chains. Supply chains shape the financial success of companies, and this book highlights how their use will lower bottomline costs and boost topline revenue. In addition, global examples are provided, including the rise of mutual supply chains in Europe; how European environmental policies promote shared supply chains; and U.S. nearshoring is rising as manufacturers of computers, machinery, fabricated metals, electronical equipment, and plastics and rubber in capital-intensive industries are returning to America. Due to its inclusion of recent trends in supply chains along with discussions on supply and demand alignment, this book provides needed insights to reduce spending, increase revenues, and become as streamlined and productive as possible in our ever changing economic climate"-- Provided by publisher.
Keywords: Business logistics; Supply and demand